Pengembangan E-Modul Interaktif IPA pada Pembelajaran Berdiferensiasi untuk Meningkatkan Berpikir Kreatif dan Mengembangkan Kreativitas Siswa - Herlina, Elin; Hindriana, Anna Fitri; Ismail, Agus Yadi (Jurnal Didaktika Pendidikan Dasar, 2025)
This research aims to improve creative thinking skills and develop students’ creativity through differentiated learning using the Science Interactive E-Module on Human Respiratory System Disorders and Diseases. This research and development uses ADDIE. The study was conducted at SMPN Unggulan Sindang with grade VIII students, 25 people in the control group and 25 in the experimental class. Data collection techniques include diagnostic assessments, validation sheets, pretest and posttest questions, questionnaires, observation sheets, product assessment sheets, and interviews. The experimental class diagnostic test results showed that the student’s learning style was 50% visual, 27% audiovisual, and 9% kinesthetic. Researchers created an interactive e-module of IPA by applying a differentiation strategy of content, processes, and products. The study results in the N-Gain 78.10 experimental class showed that this module was effective, and the paired t-test 0.001 was smaller than 2.01 at the significance level of 0.05, meaning there was a significant difference between the pretest and post-test scores. It can be concluded that using interactive e-modules can improve students’ creative thinking. Students’ creativity produces various products, namely digital and non-digital posters, tote bags, clothes, pamphlets, banners, and videos. This shows that the use of Interactive E-Modules can develop students’ creativity.